การพัฒนารูปแบบการจัดการเรียนรู้สุขศึกษาตามแนวคิดการรับใช้สังคมและการสะท้อนคิดเพื่อพัฒนาความฉลาดทางสังคมของนักเรียนมัธยมศึกษาตอนปลาย - ยอดแก้ว แก้วมหิงสา (จุฬาลงกรณ์มหาวิทยาลัย, 2019)
This research aims to 1) develop a health education learning management model based on the concept of social service and reflection to develop social intelligence of high school students. 2) To evaluate the effectiveness of the conceptual health education learning management model. Social service and reflection for the development of social intelligence of high school students. The development of the model is carried out by studying the concepts of social service and reflection, as well as information on problems and needs of learners and teachers. The data were analyzed and synthesized as a draft learning management model. And check the model quality from a qualified person The model effectiveness evaluation was conducted with two groups of students at Benjamarachanusorn School for 8 weeks. Standard deviation and t-test at the statistical significance level of .05.           The research results were found that:1) The developed health education learning management model consisted of 6 teaching steps: 1) stimulating interest in problems and needs in society 2) raising awareness in helping others 3) education of the state and problem of Community, 4) action planning, 5) practice of social service activities, and 6) reflection.2) The effectiveness results of the health education learning management model evaluation: 2.1) the experiment group had the average of the social intelligence after the experiment higher than before by statistical significance 0.5.2.2) the experiment group had the average of the social intelligence after the experiment higher than the control group by statistical significance 0.05.